Extraction of high-quality RNA from metabolite and pectin rich recalcitrant calyx tissue of Hibiscus sabdariffa L. - Hamzah, Nur Atheeqah; Yong, Christina Seok Yien; Yusuf, Umi Kalsom (Universiti Putra Malaysia Press, 2020)
Hibiscus sabdariffa L. is no stranger to the field of pharmacology, as its calyx extract is highly rich in beneficial compounds and has been demonstrated to possess antihyperglycemic, antihypertension, anticancer and antioxidant properties. Thus, it is labelled as a functional food with great health benefits and therapeutic potentials. The medicinal and nutritional components of the calyx are well reported. On the contrary, not much is known about the molecular machineries governing the biosynthesis of beneficial compounds in this plant. Obtaining good yields of high-quality RNA is crucial for the success of downstream research pertaining to molecular biology. However, the presence of high quantities of phenolic compounds, polysaccharides, mucilage and pectin in the fibrous calyx tissue poses major challenges for RNA extraction in H. sabdariffa. Here, we modified a CTABbased method for efficient extraction of high-quality RNA from the calyx tissue. High quality RNA samples having RNA integrity number of more than eight were successfully extracted. The purities of RNA samples were also confirmed by the A260/280 and A260/230 values. Subsequent successful preparation of a sequencing library using one of the RNA samples extracted via the modified CTAB method further emphasized the efficiency of this extraction protocol and quality of the RNA samples. The results showed that the modified CTAB method was effective in extracting good quality RNA from the challenging calyx tissue of Hibiscus sabdariffa L. suitable for sensitive downstream application.